2021
DOI: 10.1002/cjoc.202100582
|View full text |Cite
|
Sign up to set email alerts
|

Au(I)‐Catalyzed 6‐endodig Cyclizations of Aromatic 1,5‐Enynes to 2‐(Naphthalen‐2‐yl)anilines Leading to Divergent Syntheses of Benzo[α]carbazole, Benzo[c,h]cinnoline and Dibenzo[i]phenanthridine Derivatives

Abstract: Comprehensive Summary A gold(I)‐catalyzed 6‐endo‐dig cyclization of aromatic 1,5‐enynes was developed to synthesize 2‐(naphthalen‐2‐yl)anilines. The functional group tolerance of this cyclization was examined systematically and a possible mechanism was proposed. The derivatization of 2‐(naphthalen‐2‐yl)aniline was carried out to facile access to benzo[α]carbazole, benzo[c,h]cinnoline and dibenzo[i]phenanthridine derivatives in a divergent way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Retrosynthetically, the target molecule macarpine ( 1 ) could be disconnected into naphthol 12 ( Scheme 3 ), a key intermediate reported by Ishikawa in the total synthesis of macarpine. This intermediate could be synthesized from silyl enol ether compound 10 via the Au(I)-catalyzed cycloisomerization reaction developed by our group [ 15 ]. The compound 10 could be constructed by the Sonogashira coupling reaction from readily prepared iodoarene 8 [ 12 , 16 ] and ketone 5 , which could be synthesized by using cheap 6-bromopiperonal ( 2 ) as the starting material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrosynthetically, the target molecule macarpine ( 1 ) could be disconnected into naphthol 12 ( Scheme 3 ), a key intermediate reported by Ishikawa in the total synthesis of macarpine. This intermediate could be synthesized from silyl enol ether compound 10 via the Au(I)-catalyzed cycloisomerization reaction developed by our group [ 15 ]. The compound 10 could be constructed by the Sonogashira coupling reaction from readily prepared iodoarene 8 [ 12 , 16 ] and ketone 5 , which could be synthesized by using cheap 6-bromopiperonal ( 2 ) as the starting material.…”
Section: Resultsmentioning
confidence: 99%
“…The Au(I)-catalyzed cycloisomerization reaction of substrate 10 occurred under the catalysis of 5 mol % [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene]gold(I) chloride (IPrAuCl) and 5 mol % silver hexafluoroantimonate (AgSbF 6 ) [ 25 26 ] in anhydrous DCM at room temperature for 2 h forming a benzene ring smoothly, leading to the exclusive formation of biaryl intermediate 11 in a yield of 82%. It is worth noting that the methoxy substitution in the substrate played a crucial role in controlling the selectivity of the cycloisomerization according to our previous study [ 15 ]. It was rationalized that the electron-donating phenyl ring enabled the coordination of the alkyne with the Au + complex in the α-position, which promoted the silyl ether to attack the β-position of the alkyne to promote a 6- endo - dig cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…The authors modulated the electronic properties of the triple bond through the substituent of the right benzene ring, which further tuned the cyclization order. When there were sulfonamide substituents on the appropriate benzenes, the α-position of the alkyne activated by [Au] + induced a 5-endo-dig cyclization to produce indole intermediates (31). The enolether was then activated by a gold(I) complex and attacked by the electron-rich indole to promote the second cyclization, yielding benzo[a]carbazoles (32) by elimination of methanol and protodeauration.…”
Section: Aryne-enolether Substratesmentioning
confidence: 99%
“…In addition, several important heterocycles (38)(39)(40)(41) were synthesized in a divergent manner from that of naphthalene derivatives (37). In 2022, Liu and colleagues reported a gold(I)-catalyzed 6-endo-dig cyclization of arylalkyne-enolethers (36) to construct 2-(naphthalen-2-yl)aniline derivatives (Scheme 10) [31]. The authors found that the amine group on the right-hand benzene ring benefited 6endo-dig cyclization via an electron-donating effect to generate naphthalenes (37) after isomerization and protodeauration.…”
Section: Aryne-enolether Substratesmentioning
confidence: 99%